Tanggung Jawab Hukum Dokter Gigi Atas Terjadinya Risiko Terhadap Pemasangan Implan Gigi Pada Pasien - Mela Karina Maya Riza; Ninis Nugraheni (Jurnal Ners, 2023)
The development of dental implant science and technology has developed rapidly, the installation of dental implants is an option in replacing missing teeth. Recently, the construction of denture bridges with implant supports has been widely used and is often successful, however this does not rule out the possibility of failure in dental implant treatment. Granting additional authority to dentists with the aim of equal distribution of health services in Indonesia, there are no rules that clearly regulate the authority of dentists in placing implant dentures. This research is structured using the type of normative legal research, namely research that is focused on examining legal norms in an applicable statutory regulation related to the subject matter. The purpose of this study was to analyze the authority of dental implant placement by dentists and to analyze the legal consequences associated with the risk of dental implant placement in patients. The results of this study indicate that dental implants are the clinical authority of specialist dentists, dentists' authority in installing dental implants is limited to theoretical understanding, regarding various types of dental implant therapy, mastering application theories in dental implant cases only. Regarding the risk of failure in installing dental implants by dentists, legal remedies that can be taken by patients for losses experienced are by way of a civil suit to the local district court on the basis of liability for losses due to unlawful acts